Memahami Maria Sebagai Bunda Pengantara Doa Dalam Terang Lumen Gentium Artikel N0 62 - Trisnawati Namo (Jurnal Ilmu Agama Indonesia, 2026)
The title of Mary as the Mediatrix originates from the story of the Wedding at Cana, where Mary's maternal and caring attitude served as an intermediary for the wedding servants to Jesus. This led to the miracle of water turning into wine, which was a warm and sympathetic response of a Son to His mother. This article aims to discuss the title of Mary as the Mediatrix of prayer in the faith life of Catholics, as an expression of devotion to the Mother Mary, who faithfully accompanies the Church on its pilgrimage toward God. The method used in this research is library research, which involves searching for and collecting data or information from various relevant written sources, such as books, scientific journals, articles, official documents, and other reliable sources. The goal is to gain an in-depth understanding of Mary as the Mediatrix of prayer, so that everyone can open their hearts and consistently devote themselves to the Mother Mary. The results of this research will describe the title of Mary as the Mediatrix of prayer in the devotion of the faithful to the Mother Mary.